Do brain structural abnormalities differentiate separate forms of urgency urinary incontinence?. Issue 8 (19th April 2018) - Clarkson, Becky D.; Griffiths, Derek; Resnick, Neil M.
Abstract : Aims: Urgency urinary incontinence (UUI) is a major problem for seniors. The underlying mechanisms of disease and therapy are unknown. We sought structural brain abnormalities that might underlie the functional differences previously observed by functional Magnetic Resonance Imaging in UUI patients versus controls, or among UUI responders versus non‐responders to therapy—and thereby reveal potential disease mechanisms and therapeutic targets. Methods: Secondary study of a trial of biofeedback‐assisted pelvic floor muscle training (BFB) in 60 women (>60 yrs) with UUI, plus 11 age‐matched continent controls. Brain structural abnormalities were investigated using: (1) white‐matter hyperintensities (WMH); (2) diffusion tensor imaging (DTI) to reveal white‐matter pathways with impaired integrity; and (3) voxel‐based morphometry (VBM) to show regions of atrophy or hypertrophy. Results: WMH burden was greater in UUI patients than controls (globally and in superior longitudinal fasciculus and cingulum), suggesting a possible causal connection. WMH burden was unexpectedly greater in responders than non‐responders to BFB, and appeared to increase in non‐responders but not in responders. DTI revealed even worse integrity of the cingulum than was apparent by WMH. VBM showed parahippocampal atrophy in UUI. Conclusions: Many women with UUI have white‐matter damage that interferes with pathways critical to bladder control; they can be taught by techniques like BFB to exert stronger control over the bladder. For others, in whom abnormalities of key brain areas are less marked, UUI's cause may reside elsewhere, and therapy targeting these brain centers may be less effective than therapy targeting the bladder or other brain centers.